THE INFLUENCE OF FUNGI CONTAMINATION ON THE AVIATION FUEL AND BIOCIDE INHIBITOR - Mochammad Fierdaus; Yannie Kussuryani (Testing Center for Oil and Gas LEMIGAS, 2015)
Aviation fuel is one of the fractions of fuel oil containing hydrocarbons and trace materials in the form of organic salts. Distribution of aviation fuel to the aircraft allows the aviation fuel contaminated by water due to condensation. The presence of water, hydrocarbons and organic compounds are appropriate conditions for microbial growth. The growth of microbes among other fungi generates biomass that sould can be able block fi lter between fuel tank in aircraft to the engine and have fatal consequences for flight operation. An efforts to prevent the growth of fungi is to add biocides in aviation fuel, which is in this study using formalin. Fungi was used in this experiments consists of four species which were dominant in the aviation fuel that are: Paecilomyces sp.1, Paecilomyces sp.2, Aspergillus sp., Scytalidium sp., as will as a the of mixed cultures of four species of fungus. The concentration of formalin is used as biocide were 150 ppm, 250 ppm and 500 ppm. Parameter measured are dry weight of fungi and physical characteristic of aviation fuel including specific gravity, smoke point, freezing point, copper strip corrosion and flash point. Experiment result showed that the addition of formalin could prevent the growth of fungi in aviation fuel. For Paecilomyces sp.1 and Paecilomyces sp.2, formalin concentration of 150 ppm can prevent fungi growth in aviation fuel signifi cantly. It takes 500 ppm for Aspergillus sp. and 250 ppm for Scytalidium sp. The concentration of formalin 250 ppm and 500 ppm were inhibit the growth of mixed culture. Analysis of the physical properties of aviation fuel, showed that the use of formalin does not affect the quality of aviation fuel in all parameters tested and they meet the quality standards of aviation fuel issued by Ministry of Defence. This means that formalin can be used as biocide for aviation fuel.